HLA-B∗57 and Gender Influence the Occurrence of Tuberculosis in HIV Infected People of South India - Latha Jagannathan; Mrinalini Chaturvedi; Bhuthaiah Satish; Kadappa Shivappa Satish; Anita Desai; D. K. Subbakrishna; Parthasarathy Satishchandra; Ramasamy Pitchappan; Kamala Balakrishnan; Paturu Kondaiah; Vasanthapuram Ravi (Clinical and Developmental Immunology)
Background. Substantial evidence exists for HLA and other host genetic factors being determinants of susceptibility or resistance to infectious diseases. However, very little information is available on the role of host genetic factors in HIV-TB coinfection. Hence, a longitudinal study was undertaken to investigate HLA associations in a cohort of HIV seropositive individuals with and without TB in Bangalore, South India. Methods. A cohort of 238 HIV seropositive subjects were typed for HLA-A, B, and DR by PCR-SSP and followed up for 5 years or till manifestation of Tuberculosis. HLA data of 682 HIV Negative healthy renal donors was used as control. Results. The ratio of males and females in HIV cohort was comparable (50.4% and 49.6%). But the incidence of TB was markedly lower in females (12.6%,) than males (25.6%). Further, HLA-B*57 frequency in HIV cohort was significantly higher among females without TB (21.6%, 19/88) than males (1.7%, 1/59); P=0.0046; OR=38. CD4 counts also were higher among females in this cohort. Conclusion. This study suggests that HIV positive women with HLA-B*57 have less occurrence of TB as compared to males.